2012
DOI: 10.1111/j.2044-8287.2012.02099.x
|View full text |Cite
|
Sign up to set email alerts
|

Positive experience, self‐efficacy, and action control predict physical activity changes: A moderated mediation analysis

Abstract: What is already known on this subject? Numerous studies have shown that exercise-specific self-efficacy predicts subsequent physical activity. Prior positive experience with physical activity is suggested to be associated with exercise-specific self-efficacy. Furthermore, action control was found to be beneficial for the maintenance of physical activity. What does this study add? This study unveils the mechanisms between these social-cognitive determinants: our longitudinal results suggest that the mediation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 34 publications
3
41
0
1
Order By: Relevance
“…Experience of controlling blood sugar, lipids and blood pressure resulted in to be encouraged to continue these behaviors. Shabita (28) reported that, the feeling of pleasure of a physical activity is a supportive factor and study of Parschau (35) showed that, participants' perceptions of positive experience were associated with their subsequent self-efficacy fostering physical activity. In this regard, Shabita (28) and Sjostrom (29) mentioned that, the frequent watching of individuals' exercises is a supportive factor for doing physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Experience of controlling blood sugar, lipids and blood pressure resulted in to be encouraged to continue these behaviors. Shabita (28) reported that, the feeling of pleasure of a physical activity is a supportive factor and study of Parschau (35) showed that, participants' perceptions of positive experience were associated with their subsequent self-efficacy fostering physical activity. In this regard, Shabita (28) and Sjostrom (29) mentioned that, the frequent watching of individuals' exercises is a supportive factor for doing physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, there is strong evidence that interventions utilizing these core selfregulation techniques lead to larger short-term increases in PA (initiation) than interventions not using such techniques (10). Additional self-regulation techniques, such as focusing attention on goal pursuit and staying positive despite setbacks, have been hypothesized to contribute to the maintenance of behavioral change (9,11). Despite this, research demonstrating that interventions actually increase patients' use of self-regulation skills is scarce, and research demonstrating that this increased use of selfregulation skills indeed explains changes in PA behavior is almost nonexistent (12).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, caution regarding the behavioral outcome is warranted, as the responses indicate intention to continue attending, rather than providing objective evidence showing that attendance did continue. Nonetheless, when coupled with participants' affective responses, the results could suggest that this intention will lead to exercise adherence; for example, Parschau et al (2013) found that intentions to continue with physical activity were more likely to be translated into action when the physical activity was perceived to be a positive experience.…”
Section: Discussionmentioning
confidence: 99%